Stability of miR-126 in Urine and Its Potential as a Biomarker for Renal Endothelial Injury with Diabetic Nephropathy - Yang Liu; Guangqiang Gao; Chun Yang; Kun Zhou; Baozhong Shen; Hongyan Liang; Xiaofeng Jiang (International Journal of Endocrinology)
Background. The purpose of the present study was to assess the feasibility of using miR-126 in the urine as a biomarker for diabetic nephropathy. Methods. miRNAs were extracted from the urine samples of T2DM patients with diabetic nephropathy (DN; n=92), T2DM without DN (n=86), and 85 healthy volunteers using quantitative reverse transcriptase polymerase chain reaction (real-time polymerase chain reaction) analysis. Stability of urinary miR-126 and factors that affected the stability were assessed. A subgroup analysis was also carried out to compare the urinary miR-126 level in T2DM patients well controlled by the treatment versus those who were not well controlled. Results. Urinary miR-126 was stable when the urine samples were kept at room temperature for extended period of time, 4°C, −20°C, and −80°C for up to 12 hours or subjected to 10 freeze-and-thaw cycle. Urinary miR-126 was significantly higher in T2DM patients with DN (5.76±0.33 versus 3.25±0.45 in T2DM patients without DN). Successful treatment significantly reduced urinary miR-126 in T2DM patients with DN to 3.89±0.52 (P<0.05). Conclusion. miR-126 in the urine is stable and it could be used as a biomarker of DN and to monitor the treatment response.